ANALYSIS OF MACROECONOMIC VARIABLES ON THE RUPIAH EXCHANGE RATE BASED ON ERROR CORRECTION MODEL - Mochammad Fauzan Syaifudin; Rr Rerno Sugiharti (Transpublika Publisher, 2022)
This study aims to determine the relationship of economic growth, tax revenue, exports, imports to the rupiah exchange rate against the United States dollar in the long term and short term in the period of 1986 to 2018. The methodology used in this study is Error Correction Model (ECM). The variables used are GDP, tax revenue, export, import as independent variables, and the rupiah exchange rate against the dollar as the dependent variable. The result of this study in long run variables of exports and imports affect the exchange rate. For research result in short term GDP and tax revenue affect the exchange rate of the rupiah.